PENGARUH STRATEGI BISNIS BERUPA KINERJA PENGURUS DAN KUALITAS LAYANAN TERHADAP KEPUASAN ANGGOTA SERTA IMPLIKASINYA PADA KEBERHASILAN USAHA DENGAN PARTISIPASI ANGGOTA SEBAGAI VARIABEL MODERATOR DI KOKAPURA-JAKARTA - Bonifacio, Andres; Sihite, Mombang; Derriawan (SEKOLAH PASCASARJANA PRESS, 2021)
This study aims to analyze the effect of business strategies in the form of management performance and service quality on member satisfaction and its implications for business success with member participation as a moderating variable in Kokapura-Jakarta. The population in this study were all members of Kokapura-Jakarta, both active and inactive, with a sample of 125 people taken using non-random sampling techniques through purposive sampling method. The data analysis technique used in this research is Structural Equation Modeling (SEM) with the type of Partial Least Square (PLS-SEM) which is operated through the smartPLS 3.29 software. The results of this study prove that the management performance variables and service quality have a positive influence on member satisfaction. Then the management performance variables, service quality and member satisfaction have a positive effect on business success, and the member participation variable moderates the effect of member satisfaction on business success.